Relación entre estrés de minorías y bienestar psicológico en adolescentes, jóvenes y adultos no heteronormativos - Bergelund Echeandia, Stephanie (2022)
The objective of this report was to investigate the relationship between Meyer's minority stress factors and dimensions of eudamonic and hedonic psychological well-being in studies that considered non-heteronormative adolescent, young and adult populations. In order to accomplish a proper search in the corresponding databases ten of them were selected. In them, it was found that there is a positive relationship between most minority stressors and psychological well-being, especially proximal factors, which present a higher level of statistically significant correlation. Likewise, it was identified that self-esteem turns is a moderator to reduce the impact of distal factors of minority stress such as discrimination in psychological well-being, resilience, and social support mediate the relationship between minority stress and psychological well-being and that authenticity has a positive relationship with the psychological well-being of non-heteronormative people. We conclude that the correlations between the mentioned variables are present in all the selected studies, being important to delve into the investigation of outness in relation to psychological well-being and finally, to emphasize for the future the carrying out of investigations of structural and measurement models seeking to establish causality more than correlation.